Shadow Training Using Rubber Weights Improves The Sickle Kick Results Of Indonesian Pencak Silat Association (Ipsi) Athletes In Talang Kelapa - Fualarozi, Muhammad; Lian, Bukman; Bayu, I Made Andika (International Martial Arts and Culture Journal, 2025)
Purpose. The crescent kick is one of the important basic techniques in the martial art of Pencak Silat, used to gain quick points in a short time in every Pencak Silat match using basic technical movements with agility to move to avoid opponents in the martial art of Pencak Silat. The research method uses a variety of exercises such as using rubber weights in order to strengthen the muscles in the legs, and make the legs not stiff. The purpose of this study is to determine the accuracy when using the crescent kick for someone who studies the martial art of Pencak Silat. The research method used is an experiment with a one group pre-test post-test design. The sample in the study were IPSI (Indonesian Pencak Silat Association) Talang Kelapa martial artists, the sampling technique used was random sampling data and the sample in this study were students of IPSI (Indonesian Pencak Silat Association) Talang Kelapa martial artists totaling 10 athletes. Data analysis used was the t-test. The results of this study showed an average pretest score of 26.7 and a posttest score of 37.1, resulting in a mean difference of 10.4 between the pretest and posttest scores. The study's recommendations suggest that the rubber weights used provide significant resistance to movement, enabling athletes to overcome the resistance and change direction of their kicks.